Substrate degradation and black soldier fly larvae bioconversion performance profile on co-digested oil palm biomass-based feedstock - Mulki Salendra Kusumah; Frisda Rimbun Panjaitan; Bagus Giri Yudanto; Brahmani Dewa Bajra (PLoS ONE, 2025)
Utilization of oil palm empty fruit bunches (OPEFB) is limited due to its low nutrient value but high lignocellulose content. Black soldier fly larvae (BSFL, Hermetia illucens L.) is capable of converting organic materials into high-value products. A co-digestion strategy combining low-nutrition OPEFB and other high-nutrient oil palm by-products, i.e., oil palm kernel meal (OPKM), is an approach to enhance the digestibility of oil palm biomass by BSFL. However, the information on the degradation of cellulose, hemicellulose, and lignin in OPKM, OPEFB, and their co-digested substrates after treatment with BSFL is scarce. Therefore, this experiment evaluated the growth and bioconversion potential of BSFL grown on OPKM, OPEFB, and their mixture. Three feed treatments of 100% OPEFB, 100% OPKM, and a mixture (50% OPEFB: 50% OPKM) were given to larvae to observe growth, bioconversion potential of BSFL, and substrate degradation. In addition, the changes of the substrates morphology were analyzed by scanning electron microscope (SEM). The results show that an increase of larval biomass weight by 634% was obtained in a substrates combination of OPEFB and OPKM, with a reduction in the feed conversion ratio to 84% in twenty-five days, as compared to a 100% OPEFB feed. SEM results indicate that the surface of OPKM and OPEFB altered significantly after being consumed by BSFL. Ultimately, the current findings confirmed the potential of BSFL as bioconversion agent in the utilization of low-nutrition organic materials with high lignocellulosic content, such as OPEFB by using co-digestion method. This finding is promising to be implemented for treatment and utilization of palm oil mills by-products.